Mechanistic Study of Visible-Light-Induced Photodegradation of 4-Chlorophenol by TiO2−x Nx (0.021<x<0.049) with Low Nitrogen Concentration. (17th July 2011) - Shang, Guangfeng; Fu, Hongbo; Yang, Shaogui; Xu, Tongguang
Abstract : TiO2− x N x    ( 0.021 < x < 0.049 ) powders with low N-doping concentrations (0.021 < x < 0.049 ) were prepared by annealing commercial TiO2 (P-25) under an NH3 flow at 550°C. Regardless of UV or visible case, the photoactivities of the samples decreased as x increased, and TiO1.979 N0.021 showed the highest activity for the 4-chlorophenol (4-CP) decomposition under the visible-light irradiation. The visible-light response for N-doped TiO2 could arise from an N-induced midgap level, formed above the valence band (O 2p). Electron spin resonance (ESR) measurements and the radical scavenger technologies gave the combined evidence that the active species ( OH andO 2 − ) are responsible for the photodecomposition of 4-CP over TiO2− x N x    ( 0.021 < x < 0.049 ) under the visible irradiation. A possible photocatalytic mechanism was discussed in detail.